CEO Tenure, CEO Compensation, Corporate Social and Environmental Performance in China: The Moderating Role of Coastal and Non-coastal Areas - Khan, Talat Mehmood; Bai, Gang; Fareed, Zeeshan; Quresh, Shakir; Khalid, Zameer; Khan, Waheed Ahmed (Frontiers in Psychology, 2021)
This study uncovers a new finding of the impact of CEO tenure on corporate social & environmental performance (CS&EP) in coastal and non-coastal areas of China using fixed-effect panel data regression models. The 2SLS instrumental panel regression is used to validate the veracity of the empirical results. To this end, we extract the data of all non-financial Chinese listed firms over the period 2009-2015. By applying the multivariant framework, the findings of the study exhibit a negative and significant effect of CEO tenure on CS&EP. Moreover, this study documented that the firms, whose head office is situated in the coastal area of China tend to weaken the negative impact of CEO tenure on CS&EP, indicating that the CS&EP is more focused in coastal areas of China than that the non-coastal ones. The findings suggest that the increase in CEO's CS&EP in the early service tenure tends to increase their compensation packages. This study is useful for policymakers to link CS&EP with firm economic practices to attain sustainable-development objectives. Moreover, in the current situation, the executives can play a vital role to perform their social duties to mitigate the spread of epidemic Coronavirus (COVID-19)